Niger : Enhanced Initiative for Heavily Indebted Poor Countries Completion Point Document. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper assesses Niger's performance in meeting the requirements for reaching the completion point under the enhanced Heavily Indebted Poor Countries (HIPC) Initiative. The paper reviews the status of creditor participation and the delivery of debt relief to Niger under the enhanced HIPC Initiative, presents the results of a new debt sustainability analysis based on the reconciled stock of debt at end-2002, and provides an analysis of the sensitivity of the debt indicators to changes in macroeconomic variables. The paper also focuses on considerations pertaining to a topping up of enhanced HIPC Initiative assistance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet